Hubungan Kualitas Pelayanan Keperawatan dan Komunikasi dengan Kepuasan Pasien di Ruang Rawat Inap Interne Lantai 3 RSUD Dr. Achmad Mochtar Bukittinggi - M Fikri Zalius; Reflita Reflita; Idrawati Bahar; Efitra Efitra; Suhaimi Suhaimi (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2023)
An interview of RS.Ahmad Muchtar Bukittinggi in the year 2019 (46 %) year 2020 (92,01%) and the year 2021 (90.05%) of the data found satisfaction year of year. Ten patients were interviewed for the study, and five of them reported that nurses were unresponsive and rarely inquired about their illnesses. Research used cross sectional design. In 1November 2023 study of June 13, 2023. Research was conducted at RSUD Dr. Achmad Muchtar Bukittinggi. A population of 102 patients and samples of 50 patients. The sampling technique was purposive sampling. The collection of data uses antket. Processing with editing, coding, entry and cleaning. Analysia data univariat data with frequency and presentation. Analis bivariat uses chi-square. The results of research on nursing quality in less categories (52%), communication in less categories (52%) and patient satisfaction in unsatisfied categories (60%). The existence of the quality of nursing quality with the satisfaction of the patient is that the result of the statistics test of chi-square with the value of p = 0.024 < 0.05 And the relationship of communication with the patient's satisfaction results of chi-square statistics is produced with the value of p = 0,018 <05. The conclusion: The relationships of service quality and communication with patient satisfaction. Recommended to improve quality of nursing in particular nurse components are able to give psychological touch, motivation. while respondive components (responsiveness) that nurses respond to patient complaints more quickly and improve patient communication.